2021
DOI: 10.1007/s12055-021-01209-x
|View full text |Cite
|
Sign up to set email alerts
|

On-pump beating heart versus off-pump myocardial revascularization—a propensity-matched comparison

Abstract: Objective On-pump beating heart (OP-BH) coronary artery bypass grafting (CABG) is often undertaken as an alternative between off-pump coronary artery bypass (OPCAB) and conventional on-pump coronary artery bypass grafting (On-pump CABG), especially in India. However, outcome data following OP-BH surgery is sparse. The aim of this study was to compare the outcomes of OP-BH CABG with OPCAB. Methods From our institutional database, all patients undergoing OP-BH CABG (n = 531) were identified. A propensitymatched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In all of these compared articles, beating heart cases were shown to be superior to conventional bypass in accordance with our series. In some series, more impressive results were obtained compared to our series because of the population of the region, angiography and number of cases, but the number of parameters compared in our series is higher than in many other studies [25][26][27]. In some of the presented patient series, only hematological and biochemical evaluation was compared, and in some others only postoperative complications were compared [26,28].…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…In all of these compared articles, beating heart cases were shown to be superior to conventional bypass in accordance with our series. In some series, more impressive results were obtained compared to our series because of the population of the region, angiography and number of cases, but the number of parameters compared in our series is higher than in many other studies [25][26][27]. In some of the presented patient series, only hematological and biochemical evaluation was compared, and in some others only postoperative complications were compared [26,28].…”
Section: Discussionmentioning
confidence: 47%
“…Many articles comparing on-pump and off-pump beating heart have been published over the years [2,[25][26][27][28][29]. In some of these articles, patients with beating heart using a heart-lung machine (as in our article) were presented, while in others, beating heart cases without the use of a pump were presented and compared with the conventional bypass procedure.…”
Section: Discussionmentioning
confidence: 99%
“…It avoids cardioplegic arrest and aortic cross-clamping and provides adequate end-organ perfusion with reduced inotrope requirement. In high-risk patients, the OPBHC procedure provides an efficient way to perform surgical revascularization [10][11][12][13][14][16][17][18][20][21][22][24][25][26][27][28][29][30]. This evidence suggests that OPBHC may be the treatment of choice for patients who have experienced a cardiogenic shock after acute MI.…”
Section: Discussionmentioning
confidence: 99%
“…In high-risk patients, the OPBHC procedure provides an efficient way to perform surgical revascularization [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with ONBEAT, C-CABG was associated with similar 4 , 14 or inferior outcomes 9 . Few studies have investigated the results of OPCAB and ONBEAT, and the limited data have demonstrated comparable outcomes between the two procedures in patients with left ventricular dysfunction 15 , 16 or worse clinical outcomes in the ONBEAT population 17 .…”
Section: Introductionmentioning
confidence: 99%